Analisis Kinerja Ruas Jalan Raya Puncak (Taman Safari – Gunung Mas) Kecamatan Cisarua, Kabupaten Bogor Dengan Menggunakan Software PTV Vissim - Irenita, Novembriani; Suryobuwono, Abdullah Ade; Herdian, Tedy; Purnomo, Virgy Milleniawan; Gugat, Rudy Max Damara; Ellenlies, Ellenlies (Institut Transportasi dan Logistik Trisakti, 2022)
The increasing number of Jabodetabek residents who drive to the peak area of Bogor Regency makes the Puncak highway more crowded and congested plus the width of the road does not increase and road side disturbances are experiencing The problem faced in this study is how the peak road performance on weekdays and holidays and efforts to improve road service performance on holidays. In this study, the method that will be used is traffic microsimulation using PTV Vissim software to model according to what is happening in the field. Based on the results of the PTV Vissim simulation with the guidance of the Indonesian Road Capacity Manual (MKJI 1997), the peak road service level on holidays is in bad condition with a V/C Ratio of 0.98. The use of road capacity is less than optimal, due to various side disturbances. By making road repairs through widening from 7 meters to 12 meters, and reducing various side obstacles, it will be able to produce road services from F to C or from the average speed of 2775 smp/hour and do something when the capacity value becomes 5167 smp/hour.